Influence of organizational behavior and SIMRS on ER employees performance in dr.H.Abdul Moeloek hospital Lampung - Sri Indra Trigunarso; Isura Febrihartati (Universitas Aisyah Pringsewu, 2023)
Based on the results of the observations, the authors found that the performance of the emergency room employees at RSUD dr.H.Abdul Moeleok, Lampung Province, which was still not optimal, seen from the time that was not in accordance with the applicable SOPs so that it had an impact on the health services provided by employees. The phenomenon that occurs Organizational Behavior which is a forum for individuals, organizational structures and the environment that has not been running well is seen from individuals who have a central role who have not carried out their roles well, including in the use of available information technology as a support so that it has an impact on health services. In addition, the current Hospital Management Information System (SIMRS) is not yet comprehensive in accommodating the required transaction menu. This study aimed to determine the influence of organizational behavior and Hospital Management Information System on the performance of Emergency Department employees at dr. H. Abdul Moeloek Hospital, Lampung Province, either partially or simultaneously. The sample used was 81 employees. The method of data collection uses observation, documentation and questionnaire techniques. Data analysis used a quantitative approach with the help of SPSS statistical tools with the results of validity tests, reliability tests, regression tests and coefficients of determination tests. The results of partial hypothesis testing indicate that there is an influence of organizational behavior (X) on performance (Y) with a contribution of 82.6%. The same thing applies to the Hospital Management Information System variable (X2) on performance (Y) with a contribution of 93.7%. The results of hypothesis testing the influence of organizational behavior (X) and Hospital Management Information System (X2) on performance (Y) simultaneously show that they have an influence with a contribution of 94.2% while the remaining 5.8% is explained by factors -other factors not examined in this study.Abstrak: Berdasarkan hasil observasi, penulis menemukan bahwa kinerja pegawai IGD RSUD dr.H.Abdul Moeleok Provinsi Lampung masih belum optimal dilihat dari waktu yang belum sesuai dengan SOP yang berlaku. sehingga berdampak pada pelayanan kesehatan yang diberikan oleh pegawai. Fenomena yang terjadi Organizational Behavior yang merupakan wadah bagi individu, struktur organisasi dan lingkungan yang belum berjalan dengan baik terlihat dari individu yang memiliki peran sentral belum menjalankan perannya dengan baik, termasuk dalam pemanfaatan teknologi informasi yang tersedia sebagai dukungan sehingga berdampak pada pelayanan kesehatan. Selain itu, Sistem Informasi Manajemen Rumah Sakit (SIMRS) yang ada saat ini belum komprehensif dalam mengakomodir menu transaksi yang dibutuhkan. Tujuan penelitian ini adalah untuk mengetahui pengaruh perilaku organisasi dan Sistem Informasi Manajemen Rumah Sakit terhadap kinerja pegawai IGD RS dr.H.Abdul Moeloek Provinsi Lampung baik secara parsial maupun simultan. Sampel yang digunakan adalah 81 karyawan. Metode pengumpulan data menggunakan teknik observasi, dokumentasi dan angket. Analisis data menggunakan pendekatan kuantitatif dengan bantuan alat statistik SPSS dengan hasil uji validitas, uji reliabilitas, uji regresi dan uji koefisien determinasi. Hasil pengujian hipotesis secara parsial menunjukkan bahwa terdapat pengaruh perilaku organisasi (X) terhadap kinerja (Y) dengan kontribusi sebesar 82,6%. Hal yang sama juga berlaku pada variabel Sistem Informasi Manajemen Rumah Sakit (X2) terhadap kinerja (Y) dengan kontribusi sebesar 93,7%. Hasil pengujian hipotesis pengaruh perilaku organisasi (X) dan Sistem Informasi Manajemen Rumah Sakit (X2) terhadap kinerja (Y) secara simultan menunjukkan adanya pengaruh dengan kontribusi sebesar 94,2% sedangkan sisanya sebesar 5,8% dijelaskan oleh faktor - faktor - faktor lain yang tidak diteliti dalam penelitian ini.